IoT Sensor-based sustainable smart home management for human needs through Micro Controller - Gopal Krihsna P.; Subbarayudu Yerragudipadu; Sai Siva Kumar S.; Naveen D.; Srivastava Abhishek; Thangamani K. (E3S Web of Conferences, 2023)
Smart home technology is emerging rapidly as an exciting new paradigm. Appliances inside the home can be watched over, managed, and controlled by the consumer. Additionally, the gadgets are linked together via the internet, enabling the user to remotely control features like home lighting, air conditioner, and security systems providing sustainable approach. To aid the elderly and others with disabilities, this paper’s major goal is to teach consumers how to properly handle their household appliances. Thus, a smart home is being developed where the environmental conditions like air conditioner, television and lights adjust themselves with the person entering the room or even according to the weather conditions. Due to the complexity, in this paper an Microcontroller, LCD and other necessary materials in place of TV, AC and light are used to show that if a house consists of two or more people how the LCD will adjust itself and displays the standard required channel, likewise same LCD adjusts itself to the standard temperature required by the person and similarly adjusts itself according to the person entering into the room. Additionally, if it is raining outside the LCD will display a monsoon mood song, this is done using rain sensor. If these sensors are connected to the cloud, then the information related to the person entering the room is stored. This information can be accessed using your mobile.